2011
DOI: 10.1073/pnas.1017566108
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of constraints and caste differences in brain investment among social paper wasps

Abstract: We compared species mean data on the size of functionally distinct brain regions to test the relative rates at which investment in higher-order cognitive processing (mushroom body calyces) versus peripheral sensory processing (optic and antennal lobes) increased with increasing brain size. Subjects were eusocial paper wasps from queen and worker castes of 10 species from different genera. Relative investment in central processing tissue increased with brain size at a higher rate than peripheral structure inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 30 publications
5
52
1
Order By: Relevance
“…Overall, these results indicate that brain size does not affect brain component scaling in the same way among Polistes species, suggesting that brain size is unlikely to be a general predictor of brain composition in the genus [49].…”
Section: (A) Paper Waspsmentioning
confidence: 72%
See 4 more Smart Citations
“…Overall, these results indicate that brain size does not affect brain component scaling in the same way among Polistes species, suggesting that brain size is unlikely to be a general predictor of brain composition in the genus [49].…”
Section: (A) Paper Waspsmentioning
confidence: 72%
“…We had direct access to three of the original databases from these studies and were able to extract additional measurements not reported in the initial publications [52,57,58]. For Neotropical polistine wasp brain scaling, we used only data reported in the original publication [49]; these measurements were corrected prior to analysis owing to unit scaling errors present in the original study, as described in the electronic supplementary material. Species names and original source publications of all studied taxa are listed in the electronic supplementary material, table S2.…”
Section: Materials and Methods (A) Neuropil Investment In Social Hymenmentioning
confidence: 99%
See 3 more Smart Citations